Principle explanation and strategic schema abstraction in problem solving - Bernardo, Allan Benedict I. (Animo Repository, 2001)
This study was undertaken to examine the effects of strategic schema-acquisition tasks (problem comparison or problem construction) and the method of principle explanation (abstract or embedded principle method) on schema acquisition. Ninety-eight subjects studied a set of problems in probability, presented according to either method of principle explanation. Half the subjects in each principle-explanation group were then asked to compare analogous problems, and the rest constructed new analogous problems. To determine whether subjects generalized problem schemas, they were given new analogous problems to solve. The results showed that when the abstract principle method was used, schema acquisition was better in problem comparison; but with the embedded principle method, schema acquisition was better in problem construction. Results were discussed in relation to the importance of some fit between the presentation of problem information and the processes that will draw from or build on this information in tasks designed to allow novice problem solvers to acquire advanced problem representations.